Pakistan Under Siege Extremism, Society, and the State - Afzal, Madiha (Brookings Institution Press, 2018)
Why is Pakistan a locus for extremism? What drives the attitudes of this complex, richly textured country of more than 200 million people? Using rigorous analysis of survey data, in-depth interviews in schools and universities in Pakistan, historical narrative reporting, and her own intuitive understanding of the country, the author gives a multidimensional picture of Pakistan's relationship with extremism. -- from back cover.